Vozes e silêncios: família, trabalho e religiosidade na revitalização da memória da mulher "colona" na comunidade de Rio da Ilha - Ferraz, Ana Paula Moutinho (2014)
In the last decades, much has been reviewed and studied about the history of women, however in spite of innumerable studies about the German woman of the 19th century, little has been analyzed with regard to the woman descendant of Germans in current times, rooted in the knowledge brought by her ancestors. This thesis seeks to lay out the challenge of remembering and bringing to light the daily life of the women in the rural community of Rio da Ilha through the analysis of interviews. This study is of great value for current historical studies, not just for the fact of being descendants of an ethnic group which contributed in a very important way to the development of the southern regions, but also because they reveal information about how the women participated in the process of appropriation and cultivation in the rural environment between the 20th and 21st centuries and about the preservation of the culture and customs inherited from the first immigrants. It has as a referential the discussion about the representations produced and divulged by the women inserted in the rural context of this community based on three central foci: work, family and religiosity.